Structuralist model and general theoric studies on literature and society in Spain - Chicharro, Antonio (Tropelías: Review of Literary Theory and Comparative Literature, 1999)
The present work is a contribution to the study of the period of theoretical renovation lived in Spain starting from the decade of the sixties. In this sense, Goldmann's thought had a more than notable presence and influence in the Hispanic means, therefore the pursuil of the trajectory or its setting and criticism, in the case or the general studies about literature and society, becomes necessary. The article opens up with the treatment or what it was called the "Goldmann fashion" in order to study or the works in whith this theory critisized for their hegelian ideas. Finally, there's an approach to those theoretical studies which can be considered clearly Goldmann's influence.
Keywords: Sociology of literature; Lucien Goldmann